2008
DOI: 10.1016/j.jcm.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Separation anxiety disorder in a 13-year–old boy managed by the Neuro Emotional Technique as a biopsychosocial intervention

Abstract: Objective: To describe a case of an adolescent with separation anxiety disorder (SAD) presenting to a chiropractor for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…All adverse reactions will be recorded. In the published literature on NET there have been no documented adverse reactions [ 13 , 15 - 20 ]. It is not anticipated that participants will be exposed to any unnecessary risks.…”
Section: Methodsmentioning
confidence: 99%
“…All adverse reactions will be recorded. In the published literature on NET there have been no documented adverse reactions [ 13 , 15 - 20 ]. It is not anticipated that participants will be exposed to any unnecessary risks.…”
Section: Methodsmentioning
confidence: 99%
“…Anecdotally, it has been suggested that ADHD may be managed effectively by NET. There are published case studies on the use of NET for conditions such as hypothyroidism [ 45 ], anovulation infertility [ 46 ], polycystic ovary syndrome [ 47 ], separation anxiety disorder [ 48 ], a case series on cancer-related traumatic stress symptoms [ 49 ] and a RCT for trigger point sensitivity in chronic neck pain sufferers [ 50 ]. However, there is no validation at this time to substantiate the use of NET for children with ADHD.…”
Section: Introductionmentioning
confidence: 99%